The role of cystatin c in the prediction of outcome in hypertensive disorders of pregnancy - Saldanha, Cimona Lyn; Ara, Shabnum; Parvez, Tabassum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders of pregnancy greatly influence the maternal and foetal outcome in terms of morbidity and mortality. Complications include involvement of the kidney and progression of the disease which leads to deterioration of renal parameters and function. If left unattended, oliguria and renal shutdown are serious sequelae. Hence the importance of monitoring serum concentrations of cystatin C, creatinine and uric acid. The present study was designed to understand the variations of these markers in pregnant women in this part of India. Methods: Serum levels were therefore determined in samples from 75 healthy women at term as well as in 38 samples of patients with Gestational hypertension and in 30 patients with pre-eclampsia (PE). The values were analysed after tabulation and results subjected to statistical analysis using SPSS software programme. Results: The levels of all three components were significantly higher in pre-eclamptic patients when compared to healthy controls with the mean±SD being 1.86±0.82 vs. 1.08±0.33 for cystatin C, 0.93±0.18 vs. 0.62±0.07 for creatinine and 7.02±1.92 vs. 4.04±1.06 for uric acid respectively. In gestational hypertension, cystatin C was significantly higher, 1.42±1.1 unlike creatinine, 0.84±0.16 and uric acid, 5.26±1.40. Conclusions: In view of significant increase in serum cystatin C, creatinine and uric acid in hypertensive disorders of pregnancy compared to those of healthy pregnant women, in our study, we conclude that these parameters are of significant value if used as markers to predict the onset of GH/PE. This can be established after further and larger clinical trials.